Factores socio culturales para el desarrollo de embarazo en adolescentes en el cantón Carlos Julio Arosemena Tola enero a julio de 2018: Cultural partner factors for the development of pregnancy in adolescents in the canton Carlos Julio Arosemena Tola january to july 2018 (La U Investiga, 2018)
Objective: To compare the sociocultural factors associated with adolescent pregnancy in the Canton Carlos Julio Arosemena Tola, from January to June 2018, for which non-pregnant adolescents between the ages of 10 and 19 years were compared with pregnant adolescents of the same age.Methods: cross-sectional, prospective, observational, analytical study, in a period of 6 months, in the Canton Carlos Julio Arosemena Tola, Province of Napo, in the period from January to June 2018. We worked with the total of adolescent women which are 417, of which 10 are in gestation period. We excluded 70 adolescents from the study, of whom 68 did not meet the inclusion criteria (not nulliparous) and 2 adolescents of 19 yearswho could not be located when they were studying outside the Canton. The measures of central tendency and dispersion were established with the numerical variables, with the qualitative variables proportions were defined. Statistical analysis x2 was used as a nonparametric test to establish statistical significance. Results: it was proved that sociocultural factors such as: beginning of sexual life especially in middle adolescence, secondary education, not being a student, single marital status, nuclear family and family dysfunction are related to teenage pregnancy with a value of p
Keywords: Pregnancy; adolescents; factor; sociocultural; nulliparous